Delegating performance evaluation - Igor Letina; Shuo Liu; Nick Netzer (University of Zurich, Department of Economics, 2017)
We study optimal incentive contracts with multiple agents when performance evaluation is delegated to a reviewer. The reviewer may be biased in favor of the agents, but the degree of the bias is unknown to the principal. We show that a contest, which is a contract in which the principal determines a set of prizes to be allocated to the agents, is optimal. By using a contest, the principal can commit to sustaining incentives despite the reviewer's potential leniency bias. The optimal effort profile can be uniquely implemented by an all-pay auction with a cap, and it can also be implemented by a nested Tullock contest. Our analysis has implications for applications as diverse as the design of worker compensation, the awarding of research grants, and the allocation of foreign aid.
Keywords: D02; D82; M52; 330; Performance evaluation; delegation; optimality of contests